(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Ibuprofen lozenges were developed using liquid self-emulsifying drug delivery systems (L-SEDDS) converted into liquisolid compacts (LSCs) to enhance solubility, dissolution, and buccal drug delivery. L-SEDDS formulated with Tween 60 and Imwitor® 742 produced stable Nano emulsions in simulated salivary fluid. The optimized lozenges, selected using a Box–Behnken design, showed significantly faster dissolution and approximately 3.5-fold higher mucosal permeability than ibuprofen powder. Stability studies demonstrated that the optimized formulations maintained their physicochemical properties, dissolution profile, and mechanical strength for 6 months under ambient and accelerated storage conditions. These findings suggest that L-SEDDS-based liquisolid lozenges are a promising strategy for improving ibuprofen delivery.